2016
DOI: 10.1063/1.4943224
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-based laser-induced phosphorescence for spray diagnostics

Abstract: Laser-induced phosphorescence (LIP) is a relatively recent and versatile development for studying flow dynamics. This work investigates certain lanthanide-based molecular complexes for their use in LIP for high-speed sprays. Lanthanide complexes in solutions have been shown to possess long phosphorescence lifetimes (∼1-2 ms) and to emit light in the visible wavelength range. In particular, europium and terbium complexes are investigated using fluorescence/phosphorescence spectrometry, showing that europium-the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This technique uses ultraviolet (355-nm) laser pulses to excite ("tag") a small volume of fluid, which can subsequently be tracked by high-speed intensified cameras. Lanthanide-based phosphorescence was shown in previous work [19] to have a large decay constant (≈800 μs in water-based sprays). Furthermore, the excitation energy required is minimal, a fluence on the order of (μJ/cm 2 )/pulse.…”
Section: Spray Dispersionmentioning
confidence: 84%
See 1 more Smart Citation
“…This technique uses ultraviolet (355-nm) laser pulses to excite ("tag") a small volume of fluid, which can subsequently be tracked by high-speed intensified cameras. Lanthanide-based phosphorescence was shown in previous work [19] to have a large decay constant (≈800 μs in water-based sprays). Furthermore, the excitation energy required is minimal, a fluence on the order of (μJ/cm 2 )/pulse.…”
Section: Spray Dispersionmentioning
confidence: 84%
“…In Sec. III, the contribution of cavitation to spray growth is investigated through dispersion measurements performed using laser-induced phosphorescence of lanthanide tracers [17][18][19] and linked to cavitation events through the measured pressure fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…5 The phosphorescent compounds can be characterized by their lifetime, and the concentration of excited molecules can at any time directly be related to the liquid content. However, in previous work it was found that the luminescence lifetime itself may become time-dependent, likely as a result of evaporation 6 (see Figure 1). Especially when the timescale of the evaporation becomes similar to the timescale of the flow, the role of non-radiative decay processes (quenching) due to molecular interactions become essential for quantitative interpretations.…”
mentioning
confidence: 99%
“…All liquid in this spray was excited at the same instant, and the decrease in radially integrated luminescence over distance is more than changes in morphology can account for Ref. 6, and is likely due to evaporation. Published by AIP Publishing.…”
mentioning
confidence: 99%
See 1 more Smart Citation